Comparison of Predicted Obstacle Prediction for ALPO Type Catamaran Transport Vehicle - Wibowo Harso Nugroho; Abdul Kadir; Nanang JH Purnomo; M. Syaiful; Ahmad Yasim (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2019)
With the increase of the Decommisioning Offshore Platform in Indonesia water, a decommisioning vehicle is needed to dismantle and transport the offshore platform. Because of the operation of this vehicle to disassemble offshore platform in various offshore platform locations in Indonesian water, it is necessary to consider the vehicle main engine power by predicting the ship resistance when traveling to the offshore platform location. This paper discusses the results of several numerical prediction methods of resistance that applied on the catamaran ship type. The prediction method used for resistance calculation which based on satistical data and analytical methods from the cylindrical body theory. The resistance prediction on the decommisioning vehicles using maxsurf resistance with various methods at 12 knots service speed shows that Holtrop method produces a resistance value of 250.7 kN, the Van Oortmerssen method produces a resistance value of 955 kN, the Series60 method produces a resistance value of 210.5 kN, the Compton method produces a resistance value of 295.8 kN, the Fung method produces a resistance value of 540.6 kN, method Slender body produces a resistance value of 7036.4 kN, the Wyman method produces a resistance value of 603.2 kN and finally the last method of KR Barge produces a resistance value of 1258.5 kN. This study show that the differences of the result are significant from each of the prediction methods so that testing of the hydrodynamic model is highly recommended.